2011
DOI: 10.1111/j.1365-2745.2011.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Documenting effects of urbanization on flora using herbarium records

Abstract: Summary 1.As human populations increasingly live in cities, urban floras and the ecosystem services they provide are under increasing threat. Understanding the effects of urbanization on plants can help to predict future changes and identify ways to preserve biological diversity. Relatively few studies document changes through time in the flora of a focal region and those that do primarily address European floras. They often rely on contemporary spatial gradient studies as surrogates for changes with time. 2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 36 publications
1
44
1
1
Order By: Relevance
“…This is the case for each of the three sites in our study where these species were found. In contrast, previous studies have documented the disproportionate extirpation of high-quality species from wetlands over the last 70 years in Marion County due to land conversion [39].…”
Section: Presence Of High C-value Speciesmentioning
confidence: 60%
See 1 more Smart Citation
“…This is the case for each of the three sites in our study where these species were found. In contrast, previous studies have documented the disproportionate extirpation of high-quality species from wetlands over the last 70 years in Marion County due to land conversion [39].…”
Section: Presence Of High C-value Speciesmentioning
confidence: 60%
“…The most commonly encountered, Asian honeysuckle species in the genus Lonicera, are the subject of costly eradication efforts. They, and several other of the woody invasive species identified in our studies, were intentionally planted by the Indianapolis Parks Department in the early part of the twentieth century along boulevards throughout the city [39]. Asian bush honeysuckles are found primarily along the margins of woods in the Midwestern United States, but can spread into deeper cover.…”
Section: Non-native and Invasive Speciesmentioning
confidence: 99%
“…Numerous studies have investigated how a spatial gradient from rural, suburban to urban areas affects the diversity and abundance of organisms. Most studies have concluded that the number of species and their abundance generally decreases with increasing urbanization (Mercado Cárdenas and Buddle ), but there are exceptions particularly when invasive species (Dolan et al ) and generalist species (Magura et al , Tóthmérész et al ) are involved. The same reduction in species and their abundance toward the city centre can also be observed in temporal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Amur bush honeysuckles and other shrubs escaped from the ornamental horticultural trade are the largest physiognomic group among invasive non-native plants appearing in the flora growing outside of cultivation in Indianapolis over the last 70 years (Dolan et al 2011). This phenomenon is likely occurring in many cities and is underappreciated.…”
Section: Discussionmentioning
confidence: 99%